PATUNG LORO BLONYO DALAM KOSMOLOGI JAWA - Slamet Subiyantoro (Humaniora, 2009)
The study of ”loro blonyo” generally deals with the structure and form of the statue as a real autonomous work of art. In this article “loro blonyo” is perceived as an integral part which can not be separated from its functions and placemant. It is located in the central “senthong”, part of the structure of the “dalem” room in a traditional Javanese house. More specifically this article attempt to discuss from the point of view of Javanese cosmology what the statue of “loro blonyo” means in relation to the way of life of “sangkaning dumadi”.